Autistic traits and alcohol use in adolescents within the general population - Pijnenburg, Lisa J.; Kaplun, Anais; de Haan, Lieuwe; Janecka, Magdalena; Smith, Lauren; Reichenberg, Abraham; Banaschewski, Tobias; Bokde, Arun L. W.; Quinlan, Erin Burke; Desrivières, Sylvane; Grigis, Antoine; Garavan, Hugh; et al. (European child & adolescent psychiatry, 2023)
It has been suggested that autistic traits are associated with less frequent alcohol use in adolescence. Our study seeks to examine the relationship between autistic traits and alcohol use in a large adolescent population. Leveraging data from the IMAGEN cohort, including 2045 14-year-old adolescents that were followed-up to age 18, we selected items on social preference/skills and rigidity from different questionnaires. We used linear regression models to (1) test the effect of the sum scores on the prevalence of alcohol use (AUDIT-C) over time, (2) explore the relationship between autistic traits and alcohol use patterns, and (3) explore the specific effect of each autistic trait on alcohol use. Higher scores on the selected items were associated with trajectories of less alcohol use from the ages between 14 and 18 (b = − 0.030; CI 95% = − 0.042, − 0.017; p < 0.001). Among adolescents who used alcohol, those who reported more autistic traits were also drinking less per occasion than their peers and were less likely to engage in binge drinking. We found significant associations between alcohol use and social preference (p < 0.001), nervousness for new situations (p = 0.001), and detail orientation (p < 0.001). Autistic traits (social impairment, detail orientation, and anxiety) may buffer against alcohol use in adolescence.
Online veröffentlicht: 23. März 2022
Gesehen am 16.07.2024